Inhibitive and Adsorption Properties of Punica granatum Extract on Brass in Acid Media - S. Selvaraj2, P. Deepa Rani1* and (Journal of Phytology, 2010)
The inhibition efficacy of Punica granatum extract on the corrosion of Brass in 1N HCl has been studied by mass loss measurments at various time and temperature. The inhibition efficiency is markedly higher in HCl environment with addition of Punica granatum extract compared with those in the inhibitor free solution. The inhibition efficiency increased with increase of inhibitor concentration but decreased with rise in temperature and time. Based on the values of activation energy, free energy of adsorption and variation of inhibition efficiency with temperature, a physical adsorption mechanism is proposed for the adsorption of Punica granatum on the surface of Brass. It is found to follows Langmuir and Fremkin adsorption isotherms. The alcoholic extract of bio-inhibitor and the corrosion product (with inhibitor) is analysed by UV, IR and XRD studies leads to the bio-inhibitor as an adsorption inhibitor. Key words: Corrosion inhibition, Brass, Punica granatum, Isotherm <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">P. Deepa Rani and S. Selvaraj. Inhibitive and Adsorption Properties of Punica granatum Extract on Brass in Acid Media. J Phytol 2/11 (2010) 58-64